The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1977
DOI: 10.2134/agronj1977.00021962006900040032x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Oxygen Effects in Soil on Nutrient Uptake in Jojoba Seedlings1

Abstract: Jojoba (Simmondsia chinensis), a woody shrub, produces seeds which have several potential uses. The objectives of this experiment were to study the effects of soil temperature and soil oxygen supply on the nutrient uptake of the jojoba plant. Presently, there is little information on effect of soil physical factors on plant nutrients. The study was conducted in a greenhouse with constant temperature tanks to maintain root temperatures at 21, 27, and 33 C. Soil oxygen supply to the roots was controlled by contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…The larger yield increase from starter fertilization at the late planting date compared with two earlier dates was unexpected. Previous research had indicated that cool soil temperatures, which generally occur early in the season, are associated with positive responses to starter fertilizer (Beauchamp and Lathwell, 1967;Reyes et al, 1977). Temperatures in 1991 were generally above the longterm average, but the higher than normal rainfall in April ( Table 1) may have affected the response to starter :j: Plants at harvest.…”
Section: Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger yield increase from starter fertilization at the late planting date compared with two earlier dates was unexpected. Previous research had indicated that cool soil temperatures, which generally occur early in the season, are associated with positive responses to starter fertilizer (Beauchamp and Lathwell, 1967;Reyes et al, 1977). Temperatures in 1991 were generally above the longterm average, but the higher than normal rainfall in April ( Table 1) may have affected the response to starter :j: Plants at harvest.…”
Section: Yieldmentioning
confidence: 99%
“…a P starter fertilizer. Others have shown that starter fertilizer responses are more likely under lowtemperature conditions (Beauchamp and Lathwell, 1967;Reyes et al, 1977). Highest ovemll yield occurred at the 15 March planting date, where starter fertilization increased yield 1.0 Mg ha-1 • The low yield and lack of starter response at the 1 April planting date• may have been related to a southern green stink bug [Nezara viridula (L.)] infestation.…”
Section: Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In this direction, addition of 50 kg N and/or 50 kg P 2 O 5 kg ha −1 for three consecutive years induced no effect appeared in vegetative growth. Osman and AboHassan (1998), Reyes et al (1977), Feldman et al (1984), and Yermanos (1982) found that the root length of the jojoba plants enables it to draw nutrients from much deeper soil profiles, root type (fibrous or tap root), and soil condition. Element of nitrogen is very important in agriculture subject because it led to increase the crop yield.…”
Section: Introductionmentioning
confidence: 99%
“…Lovenstein (1985) estimated that about 58, 11, 22, 4 and 4-kg ha -1 of N, P, K, S and Mg are needed for the production of 3 t of seeds ha -1 from Jojoba plantations. Adams et al (1977) and Reyes et al (1977) indicated that response of Jojoba to fertilizer applications depends on the root type (tap vs. fibrous), soil temperature and season of growth. According to these workers rooted cuttings, having fibrous root system, unlike young seedlings with a tap root system, did not respond to fertilizer applications.…”
Section: Introductionmentioning
confidence: 99%